Posągi jako źródła nowej epistemologii (przypadek Michela Serresa) - Trzeciak, Katarzyna (Przestrzenie Teorii, 2017)
The article attempts to read the metaphor of the statue in Michel Serres’ philosophical discourse. Sculpture understood in the broad sense, as Serres proposes in Statues: The Second Book of Foundations, enables him to trace a whole array of concepts in western thought, and to make the statue itself a model of new cognition, extending beyond binary oppositions and open to unpredictability and a lack of continuity. For Serres a statue also offers the possibility to cross the boundaries of science and the humanities, and consequently to become, at the same time, both a critical and utopian figure.